A proteolytic fragment of histone deacetylase 4 protects the heart from failure by regulating the hexosamine biosynthetic pathway - Lehmann, Lorenz; Jebessa, Zegeye Hailu; Kreußer, Michael; Horsch, Axel; He, Tao; Kronlage, Mariya; Dewenter, Matthias; Sramek, Viviana; Oehl, Ulrike; Krebs-Haupenthal, Jutta; Ritterhoff, Julia; Finke, Daniel; et al. (Nature medicine, 2018)
A proteolytically derived fragment of the epigenetic regulator HDAC4 protects the heart through transcriptional repression of the hexosamine biosynthetic pathway, thereby inhibiting protein O-GlcNAcylation and maintaining normal calcium handling and contractility of cardiomyocytes.